2008
DOI: 10.1159/000163848
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Hemodiafiltration Session with On-Line Regeneration of the Ultrafiltrate on Oxidative Stress

Abstract: Background: The influence of a dialysis session using hemodiafiltration with on-line regeneration of the ultrafiltrate (HFR) is compared with that of a conventional hemodialysis session with polysulfone (HD-PS) and with a group of healthy individuals. Methods: Total antioxidant capacity (TAC), antioxidants, i.e., superoxide dismutase (SOD) glutathione peroxidase (GPX), reduced glutathione (GSH) and catalase, and biomarkers of oxidative stress were evaluated in plasma, whole blood and lymphocytes. Results: The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 45 publications
1
14
1
Order By: Relevance
“…Also, clearance of cytokines by highflux dialysis treatment has recently gained intense interest, especially in patients with septicemia [24] . HDF and high-flux HD have been associated with better outcomes in large studies [23] and also cause less oxidative stress than HD with low-flux polysulfone membranes [25] . The in vivo data in the present study are in line with our previously reported data on the impact of dialysis membrane permeability on neutrophil transmigration properties in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Also, clearance of cytokines by highflux dialysis treatment has recently gained intense interest, especially in patients with septicemia [24] . HDF and high-flux HD have been associated with better outcomes in large studies [23] and also cause less oxidative stress than HD with low-flux polysulfone membranes [25] . The in vivo data in the present study are in line with our previously reported data on the impact of dialysis membrane permeability on neutrophil transmigration properties in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…A comparative study of HFR and low-flux bicarbonate HD revealed that HFR reduced not only the plasma level of oxidized low-density lipoprotein (LDL), but also the mRNA production of p22phox and PAI-1 (palsminogen activator inhibitor 1), whose protein expressions are known to be closely related to inflammation and oxidative stress (Calo et al, 2007). Furthermore, plasma total antioxidant capacity (TAC) and antioxidant enzymes activities were found to be lower for HFR than high-flux HD (Gonzalez-Diez et al, 2008). However, contrary results have also been presented.…”
Section: Paired Filtration Dialysis With Endogenous Reinfusion (Hfr)mentioning
confidence: 99%
“…Total antioxidant capacity and glutathione peroxidase activity were increased and reactive oxygen metabolites, including pentosidine, advanced oxidation protein products (AOPPs) and oxidized LDL, were decreased in patients undergoing HDF compared to HD [59,60,61,62]. In addition, the p22phox subunit of NADPH oxidase—one of the enzymes possibly partly responsible for the increased oxidative stress—was found to be less expressed in patients on HDF compared to patients on HD [62].…”
Section: Influence Of Different Dialysis Therapies On Genomic Damamentioning
confidence: 99%
“…In addition, the p22phox subunit of NADPH oxidase—one of the enzymes possibly partly responsible for the increased oxidative stress—was found to be less expressed in patients on HDF compared to patients on HD [62]. Last, but not least, the amount of the oxidative 8-oxodG base modification, quantified in lymphocytes after a dialysis session, was significantly lower in HDF than in HD [60], supporting the hypothesis that the HDF procedure is superior not only in eliminating molecules generating oxidative stress or produced by oxidative stress, but itself causes less oxidative stress than HD [63]. …”
Section: Influence Of Different Dialysis Therapies On Genomic Damamentioning
confidence: 99%